ORGANOLEPTIC TEST AND ANALYSIS OF IRON (FE) ICE CREAM WITH MORINGA LEAF JUICE - Evynurachma; Dwi Hendriani; Rosalin Ariefah Putri (The Islamic Education and Multiculturalism Foundation, 2023)
Moringa is a type of food that is very useful and contains many nutrients, both macronutrients and micronutrients that have been widely used in dealing with malnutrition especially in pregnant women and can improve the immune system. In developing countries Ice cream is the most popular food and is very popular with all circles of society because it tastes very good and, soft texture and contains substances nutrition and can be one of the media in improving nutrition. To determine the acceptability and analysis of the Fe content of ice cream with the addition of Moringa leaves. This type of research is experimental with pre test and post test group designs, which are given adding Moringa leaves to the manufacture of ice cream with some concentration. Research on texture, as well as aspects of taste and value weighting results, the best formulation of ice cream with the addition of Moringa leaves is F1 compared to F2, F3, and F4, namely with a value of F1 60, F2 46.06, F3 42.01, F4 33.29, although when compared to F0 (ice cream krontrol) the value is lower at 54.65. Results of Iron (fe) analysis Ice cream with the addition of Moringa leaves increased from 3.3% to 4.1% This happened after the addition of 30 grams of Moringa leaves. From the results of the acceptability research on aspects of color, aroma, texture, and taste, the best formulation of ice cream with the addition of 30 gr Moringa leaves is F1 compared to F2, F3, and F4, namely with a value of F1 52.86, F2 42.86, F3 42.01, F4 33.29, although when compared to F0 (ice cream control) the value is lower at 54.65. There is an increase in Iron (Fe) content in ice cream with the addition of 30 g Moringa leaves which is 0.0888 g, compared to without the addition of Moringa leaves or 0 g which is 0.0686 g.